Perspektif Pendidikan Moral Syekh Muhammad Syakir dalam Pembentukan Nilai-Nilai Etika Generasi Z - Shofiyuddin, Moh.; Al Amin, Habibi (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2025)
Moral education plays a strategic role in shaping character and ethical values, especially for Generation Z, which is growing up in an era of globalization and digital technological advancement. This study examines the thoughts of Sheikh Muhammad Syakir, a classical Islamic education figure, who offers moral education principles that are relevant for instilling ethical values in Generation Z. Through a library research approach, this study analyzes the essence of Sheikh Muhammad Syakir's thoughts and their relevance in the context of contemporary education. The findings indicate that principles such as respect for parents, maintaining one's speech, avoiding arrogance, and emphasizing trustworthiness, honesty, and humility are crucial in forming a well-rounded and sustainable character. Furthermore, adaptive and effective moral education can assist Generation Z in facing complex social and academic challenges while developing integrity and social responsibility. Thus, this research underscores the importance of integrating moral values into both formal and non-formal education to equip Generation Z with ethical and responsible character.